Effects of different synthesis methods on physical properties of La0.85K0.15MnO3 - Pan, Kai Yap (2013)
The structure, microstructure, magnetic and electrical properties of La0.85K0.15MnO3 polycrystalline manganites synthesized via three methods: solid state (SS), sol-gel (SG) and co-precipitation (CP) and then sintered with various sintering temperature and synthesized were investigated and reported. XRD patterns of all SS and SG sintered samples showed a pure perovskite phase of hexagonal structure while CP samples that sintered at 1000˚C and 1100˚C showed the appearance of secondary phases. SG samples showed pure phase at the calcination temperature of 700˚C while SS and CP methods showed same structure at 800˚C. SEM micrographs displayed an increase of average grain size with sintering temperature. Nevertheless,formation of melt-like structure grains was occurred at 1100˚C, for all methods. The room temperature magnetization curves of all SS and SG samples showed ferromagnetic ordering behavior. The magnetization was increased with the increasing of average grain sizes. Conversely, CP samples sintered at 1000˚C and 1100˚C showed paramagnetic behavior due to the presence of secondary phases and exhibited less content of potassium. By comparing the magnetization through synthesized techniques, SS sample had the highest magnetization while CP synthesized sample obtained lowest magnetization. The Curie temperature (Tc) decreased with the increase of sintering temperature. This might associated with the elongation of Mn-O bond length and narrowed of Mn-O-Mn bond angle that had the responsibility in double exchange mechanism. The electrical transport properties at zero field of SS and SG samples showed that the metal-insulator transition temperature (Tp) increased with the increase of sintering temperature. The grain growth promotion and decrease of grain boundaries caused these phenomena because grain connectivity was improved when the sintering temperature was increased. Abnormal electrical curve was observed in CP samples with sintering temperature of 1000˚C and 1100˚C. This might affected by the vaporization of K and the occurrence secondary phases on the structure. By comparing Tc and Tp through synthesized techniques, SS method exhibits highest Tc and Tp while CP sample shows lowest Tc and Tp. This may due to the shortest Mn-O bond length, widest Mn-O-Mn bond angle and largest average grain size that possessed by SS samples. All samples exhibited MR effect at room temperature with the raised of field from 0 to 1T. The lack of DE mechanism in CP samples sintered at 1000˚C and 1100˚C due to the vaporization of potassium content causing low MR effect on that both samples. Pure LKMO system exhibited ferromagnetic-insulator (FI) phase at room temperature.